A RE-EXAMINATION OF INDIGENOUS VALUES AS PANACEA FOR LEADERSHIP CHALLENGES IN NIGERIA - CHIAKOR ALFRED; EUGENE ALIEGBA; RUTH CALEB LUKA (International Studies Journal)
Nigeria is challenged by leadership crises, the intensity of which is tearing the country at its seams. This article highlights the architecture of the indigenous values, which infused merit, integrity, accountability and competence and argues its relevance to the current leadership challenges in modern political developments in Nigeria. It further examines the crises of leadership in the face of the declining absence of positive political values, which were structurally embedded in the indigenous value systems of Nigerian societies. The articleaffirms the imperative to re-examine indigenous value sets to mitigate the numerous crises that has engulfed the leadership in Nigeria. Using the political economy framework of analysis, the write up provides the historical foundations and relationship between leadership within Nigeria’s pre-colonial societies, and has compared same to the leadership question in modern democratic practice. It concluded and recommends the consideration of some indigenous values, especially its leadership recruitment system that entrenched merit, integrity, honesty, accountability and capacity as the sine qua non for achieving quality leadership, good governance and development. The write up also recommends the adoption of traditional mechanismsin the enforcement of anti corruption, transparency and accountability by the leadership and political elite.